2020
DOI: 10.1186/s10033-019-0426-7
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Bio-tensegrity Manipulator with Multi-degree of Freedom and Variable Structure

Abstract: Conventional manipulators with rigid structures and stiffness actuators have poor flexibility, limited obstacle avoidance capability, and constrained workspace. Some developed flexible or soft manipulators in recent years have the characteristics of infinite degrees of freedom, high flexibility, environmental adaptability, and extended manipulation capability. However, these existing manipulators still cannot achieve the shrinking motion and independent control of specified segments like the animals, which hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Figure . 5, Figure 6 and Figure 7 are compared, and it can be found that there is little difference between the changes of joints 5 and 6. This is because 6  is determined by 2  and 5  together in the calculation, while in the process of moving, the change of 5  is much greater than that of 2  , and the effect on 2  is much less than that of 5…”
Section: Motion Simulation Of Manipulatormentioning
confidence: 99%
See 1 more Smart Citation
“…Figure . 5, Figure 6 and Figure 7 are compared, and it can be found that there is little difference between the changes of joints 5 and 6. This is because 6  is determined by 2  and 5  together in the calculation, while in the process of moving, the change of 5  is much greater than that of 2  , and the effect on 2  is much less than that of 5…”
Section: Motion Simulation Of Manipulatormentioning
confidence: 99%
“…For example, the large amount of computation leads to more response time than the general manipulator, and the complexity shows that even if the algorithm can be optimized to reduce the amount of computation, it is difficult to apply to the actual obstacle avoidance. The second method is local control, which is different from global planning obstacle avoidance in that it is based on the control level and solves the obstacle avoidance problem through the bottom control, which involves a small amount of calculation and more flexible calculation [5]. The local control method is proposed for the redundant manipulator to perform obstacle avoidance, and the critical point in the obstacle avoidance is kept away from the obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…Although many advanced control methods, such as adaptive control [7], neural network control [8], and variable structure control [9], can be applied to human-robot cooperation manipulator control system, they all have some limitations. Deng [10] developed a novel finite-time command filter backstepping method, which allows the traditional command filter backstepping control and ensures the finite-time convergence.…”
Section: Introductionmentioning
confidence: 99%
“…Using the force density method to solve the inverse kinematics, a modular tensegrity robot inspired by the vertebrae morphologies to grasp objects was developed [15]. An investigation on the motion patterns of a flexible biotensegrity manipulator mimicking the shrinking behavior of octopus tentacles was also conducted [16]. Although many studies of biotensegrity robots have been conducted through numerical and experimental works, the static and kinematic problems are hardly solved due to highly constrained coupling systems, particularly when subjected to an external load [17].…”
Section: Introductionmentioning
confidence: 99%